Shadow Hand - Sharma, Dhruv; Tokas, Kirti; Puri, Aviral; Sharda, Krishna (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2014)
The shadow hand is an advanced humanoid hand that uses hand movements and trajectory tracking to control the motion of shadow hand. The shadow hand will be integrated with 40 Air Muscles or 20 DC motors with the help of which it will move. The muscles will be in accordance allowing the hand to be used around soft or fragile objects. The hand will be shaped with touch sensors on finger tips to offer high sensitivity. This shadow hand robot has its various applications in household work, telepresence operations, bomb disarmament, military and medical purposes. Through this shadow hand bot we would also be able the problems faced by handicapped people.